Development of Geographic Learning Design Using Information Technology with Constructivistic Approach (Blended Learning) - Delli Hardianti; Yurni Suasti; Ernawati Ernawati (International Journal of Educational Dynamics, 2019)
The development of the world of education is currently increasing, one of which is the emergence of E-learning and constructivism learning designs that explore the potential, abilities, and insights of students in a broad and structured manner through Blended Learning. The method used in this writing is a literature study using several articles as material to create new articles. In this study, the author writes by referring to several articles that have been reviewed. Results The use of learning designs that combine face-to-face methods with learning designs using IT becomes an alternative when many students feel bored with the current learning designs. The face-to-face learning system that has undergone a change from traditional (lectures) to a more modern one is the constructivist approach. The use of the Blended Learning method that combines the design of Constructivism Learning with E-Learning makes the KBM process run better and optimally.